Modeling the Recovery Dynamics of Coronal Dimming across Solar Activity Phases: A Theoretical Approach - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2025)
This study investigates the recovery of dynamics of coronal dimmings across solar activity phase. The impact of plasma density, magnetic field evolution, and temperature distributions on the formation of core and secondary dimming regions in solar and astrophysical plasma environments. Using advanced simulation techniques, we modeled the evolution of plasma density and temperature, revealing significant temperature gradients and distinct density profiles.. The results show a marked decrease in plasma density at the core regions, surrounded by secondary dimming zones, consistent with observed phenomena in solar flares and coronal mass ejections (CMEs). Thermal conduction plays a crucial role in maintaining high temperatures at the core, while radiative cooling is prominent in the outer plasma regions, contributing to the cooling and dimming effects. The study also highlights the importance of magnetic flux tubes in shaping these plasma structures, with the symmetry of the density and temperature profiles supporting the confinement of these structures. These findings contribute to a better understanding of the physical processes governing plasma behavior in astrophysical contexts such as solar flares, stellar atmospheres, and galaxy clusters. Additionally, our results emphasize the need for further multi-dimensional simulations and empirical observations to validate and expand upon these findings, ultimately providing insights into space weather phenomena and other plasma-related processes in the universe. The study's findings have potential implications for space weather forecasting, stellar physics, and plasma dynamics in various astrophysical systems.